Faktor Keberhasilan Program Kelompok Usaha Bersama - Melly Fitria; Mochamad Fachrurozi (Journal of Innovation in Management, Accounting and Business, 2023)
The Joint Business Group (KUBE) is a business group assisted by the Indonesian Ministry of Social Affairs which was formed from several assisted families to run Productive Economic Businesses and Social Welfare Businesses in the context of business independence, improving community welfare. With this group, it is hoped that the welfare of its members can increase. This study aims to analyze the factors that determine the success of the Joint Business Group (KUBE) program in Sambit Regency. The research sample was determined by purposive sampling with the consideration that KUBE meets the requirements to be sampled, namely KUBE which is still active. The methodology in this study uses quantitative research with multiple linear regression analysis techniques. This study examines each variable by testing the hypothesis and the coefficient of determination. The results showed that the determining factors for the success of KUBE in the form of venture capital, experience in entrepreneurship and the role of mentors had a significant effect on the success of the KUBE program. The success of KUBE will make a major contribution to the government in achieving the absolute poverty rate reduction target.